Molecular basis of disease resistance in banana progenitor Musa Balbisiana against Xanthomonas Campestris pv. Musacearum - Tripathi, L.; Tripathi, J.; Shah, T.; Muiruri, K.S.; Katari, M. (Springer, 2019)
Banana Xanthomonas wilt disease, caused by Xanthomonas campestris pv. musacearum (Xcm), is a major threat to banana production in east Africa. All cultivated varieties of banana are susceptible to Xcm and only the progenitor species Musa balbisiana was found to be resistant. The molecular basis of susceptibility and resistance of banana genotypes to Xcm is currently unknown. Transcriptome analysis of disease resistant genotype Musa balbisiana and highly susceptible banana cultivar Pisang Awak challenged with Xcm was performed to understand the disease response. The number of differentially expressed genes (DEGs) was higher in Musa balbisiana in comparison to Pisang Awak. Genes associated with response to biotic stress were up-regulated in Musa balbisiana. The DEGs were further mapped to the biotic stress pathways. Our results suggested activation of both PAMP-triggered basal defense and disease resistance (R) protein-mediated defense in Musa balbisiana as early response to Xcm infection. This study reports the first comparative transcriptome profile of the susceptible and resistant genotype of banana during early infection with Xcm and provide insights on the defense mechanism in Musa balbisiana, which can be used for genetic improvement of commonly cultivated banana varieties.